Refraksi dan Alinasi Pengangkatan Hakim Konstitusi - Fajriyah, Mira (Jurnal Konstitusi, 2015)
The Justice appointment of The Constitutional Court is an entry point of the independence and impartiality of The Constitutional Court in Indonesia. There is some refraction on the mechanism of the Justice appointment of The Constitutional Court either in the juridical case also in the socio-juridical case. In the juridical  case, there is a substantive regulation flaw as be found in UUD N RI 1945, UU KK dan UU MK. In the socio-juridical case, there is three discourse points to change the mechanism of the Justice appointment of The Constitutional Court. Those discourse points consist of the context of requirement, the ultimate right enforcement of DPR, Presiden and Mahkamah Agung in the Justice appointment of The Constitutional Court which dealing the democratic principle, and the last is about the ideal composition of The Constitutional Court’s Justice based on their political background. Those juridical and socio-juridical cases have to guiding back to the characteristic of The Constitutional Court which will produce the alignment of The Justice appointment of The Constitutional Court. The concept is a juridical alignment that changing the regulation of mechanism of the Justice appointment of The Constitutional Court to fulfill the law hierarchy system and also to accommodate the socio-juridical case substantively and democratically.